THE CONSTRUCTION LEARNING MEDIA AND LEVEL OF STUDENTS' MATHEMATICAL COMMUNICATION ABILITY - Dian Fitri Argarini; Nok Izatul Yazidah; Anik Kurniawati (IKIP Siliwangi and I-MES, 2020)
This study aims to look at the effect of the use of instructional media on student learning achievement in terms of students' mathematical communication. The learning media in this study are textbooks with a constructivism approach that has been validated and tested previously. This study will compare the learning achievements of students who learn using constructivism learning models with constructivism media, constructivism learning models without media, and direct learning. This is a quasi-experimental research with a 3 × 3 factorial design. It involved junior high school students in Malang district as the research population. Based on the hypothesis, it is revealed that : (1) students who learn using constructivism approach with constructivist media had better performance than other groups, (2) students with high mathematical communication had higher learning achievement than students with moderate and low communication skills, ( 3) based on the category of high, moderate and low mathematical communication, students with constructivist learning and constructivist media gained better achievements, (4) in the constructivist learning group using constructivist media, constructivist learning without media, and direct learning, students with high mathematical communication gained better achievement than students with moderate and low mathematical communication